Sleep structure of short-term insomnia disorder with mild cognitive impairment in older adults and their correlation with cognitive function: a case-control study - Zeng, Jinkun; Wei, Jia; Qi, Ruobing (Frontiers in Aging Neuroscience, 2025)
ObjectivesThis study seeks to delineate the sleep architecture characteristics in older adults with short-term insomnia and mild cognitive impairment (MCI) and to explore their association with cognitive performance.MethodsNinety elderly individuals with short-term insomnia were enrolled and stratified into two cohorts based on their Montreal Cognitive Assessment (MoCA) scores: the Short-Term Insomnia Group (STID) comprising 35 participants and the Short-Term Insomnia with Cognitive Impairment Group (STID-MCI) with 55 participants. Demographic data, Pittsburgh Sleep Quality Index (PSQI), MoCA, Hamilton Depression Rating Scale (HAMD-17), Hamilton Anxiety Rating Scale (HAMA), and polysomnography (PSG) parameters were compared between groups. Correlations between MoCA scores and PSG metrics were also analyzed.ResultsNo significant disparities were noted between groups in terms of HAMD-17, HAMA, and PSQI scores (p > 0.05). However, marked differences were identified in MoCA scores and its subdomains (p < 0.05). Significant variations were also observed in the duration and proportion of slow-wave sleep (N3) between groups (p < 0.05). In STID-MCI patients, memory scores correlated positively with N3 duration and percentage (p < 0.05), while verbal functions and attention were positively associated with rapid eye movement (REM) sleep duration.ConclusionThis study highlights the potential of PSG in the clinical assessment of cognitive function and underscores the need for targeted interventions to improve sleep quality in this vulnerable population.